Report from the International Conference “The problems faced by youth. The perspective of education-assistance programmes” Faculty of Educational Studies AMU Poznań Poznań, 16th May 2018 - Schmidt, Anna (Studia Edukacyjne, 2018)
Report from the International Conference “The problems faced by youth. The perspective of education-assistance programmes” Faculty of Educational Studies AMU Poznań Poznań, 16th May 2018